2021
DOI: 10.1097/qad.0000000000002873
|View full text |Cite
|
Sign up to set email alerts
|

Normal structural brain development in adolescents treated for perinatally acquired HIV: a longitudinal imaging study

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…We found no association between WMH and Lp(a). The low absolute volume of WMH in our participants could have hampered the detection of this association [ 26 ]. We also found no association between white matter microstructure and Lp(a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found no association between WMH and Lp(a). The low absolute volume of WMH in our participants could have hampered the detection of this association [ 26 ]. We also found no association between white matter microstructure and Lp(a).…”
Section: Discussionmentioning
confidence: 99%
“…We also found no association between white matter microstructure and Lp(a). We assessed this association as previous studies reported mixed results and suggested that PHIV children possibly have a higher prevalence of white matter microstructure damage compared to matched controls [ 26 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were group differences in the pallidum at baseline, these attenuated over one year and group effects were considered minor by the authors; however, within the group with PHIV intriguing associations of CD4 count with pallidum shape and volume were observed. Similarly, findings from the Dutch NOVICE cohort suggest comparable maturational processes during later adolescence [75]. Longitudinal structural MRI and diffusion tensor imaging (DTI) were performed over 4.6 years for 20 youth with and 23 without HIV (mean age 18 and 17, respectively, at the follow-up visit).…”
Section: Selected Recent Neuroimaging Studies Among Adolescents and Y...mentioning
confidence: 96%
“…16 Although evidence suggests that children and adolescents with PHIV manifest subtle brain alterations compared with healthy controls, these studies did not match for, or report differences in, early-life characteristics, such as nutrition history or adoption status. [8][9][10]14,16 These factors are important because brain maturation is at a critical stage in early life 17 and adoption has been associated with malnutrition and neglect, 18 which, in turn, have been associated with altered brain development. 19,20 In the Netherlands, the majority of adolescents with PHIV have been adopted.…”
mentioning
confidence: 99%